Science Education Optimization: Evaluating the Impact of Science Kits on Improving Teacher Competence: Optimasi Pendidikan Sains: Evaluasi Dampak Kit IPA pada Peningkatan Kompetensi Guru - Darmayanti , Ni Wayan Sri; Suantara, I Wayan; Astuti, Ni Putu Eni; Partini, Ni Ketut Sri; Wulandari, Kadek Yuni; Dari, Ni Komang Ayu Ulan (Universitas Muhammadiyah Sidoarjo, 2024)
The researchers used a quantitative descriptive approach. The objective of the study is to determine how well teachers use KIT media in science learning. Ten teachers at Elementary School 7 Manukaya were used as research subjects. The research objective is to determine how well teachers use KIT media in science learning. A questionnaire was used. Of the ten teachers who were assessed for improving their ability to use KIT media, eight received positive results, while the other two received less positive results. The researchers examined the data using the Gain Score scale. Overall, the average N-Gain improvement was 0.7, the interpretation percentage was 75%, and included in the moderate improvement category.